1986
DOI: 10.1051/rnd:19860424
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in small intestine and liver during postnatal development in the lamb

Abstract: Both the small intestine and liver account for 33 % to 49 % of total protein synthesis in the rat, from 3 to 105 weeks of life . Very little information is available, however, on the earliest stages of postnatal development. We describe here changes in protein synthesis before weaning in the small intestine and liver of one and five-week old lambs. The same large dose method was used for both ages to overcome problems that arise when measuring protein synthesis in these tissues (McNurlan et al., 1979

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…For the effect of age on tissue protein synthesis, many investigators reported that protein synthesis declined in specific tissues (e. g., liver or muscle) and the whole body throughout development in mammals after weaning (11)(12)(13)(14). We demonstrated that the rate of protein synthesis in the brain decreased with age in rats after weaning (15).…”
Section: Concentrationsmentioning
confidence: 99%
“…For the effect of age on tissue protein synthesis, many investigators reported that protein synthesis declined in specific tissues (e. g., liver or muscle) and the whole body throughout development in mammals after weaning (11)(12)(13)(14). We demonstrated that the rate of protein synthesis in the brain decreased with age in rats after weaning (15).…”
Section: Concentrationsmentioning
confidence: 99%
“…The most commonly studied tissues include skeletal muscle, liver and gastrointestinal tissues. Protein synthesis is affected by a variety of physiological conditions imposed by lactation (Vincent & Lindsay, 1985), cold temperatures (Thompson et al 1987), endocrine manipulation (Vernon, 1989), age (Attaix et al 1986). diet composition and level of intake (Garlick et al 1985;Boisclair et al 1987;Jepson et al 1988) and sepsis (Hasselgren et al 1986) (Tables 2 and 3).…”
Section: Protein S Y N T H E S I Smentioning
confidence: 99%
“…Protein synthesis in the brain is also sensitive to the alteration of dietary amino acid composition ( , ) in young rats. Many investigators have reported that protein synthesis declined in specific tissues (e.g., liver or muscle) and in the whole body throughout development in mammals after weaning ( ). We have demonstrated that the rate of protein synthesis in the brain decreased with age in rats after weaning ().…”
Section: Introductionmentioning
confidence: 99%